2009
DOI: 10.1111/j.1530-0277.2009.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Episodic Drinking and Alcohol Consumption in French Colleges: The Role of Perceived Social Norms

Abstract: Background: The effect of normative perceptions (social norms) on heavy episodic drinking (HED) behavior is well known in the U.S. college setting, but little work is available in other cultural contexts. The objective of this study is therefore to assess whether social norms of alcohol use are related to HED in France, taking account of other influential predictors.Methods: A cross-sectional survey was carried out among 731 second-year university students in the Paris region to explore the role of 29 potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 49 publications
4
29
0
Order By: Relevance
“…Our findings, that a high proportion of students estimated the alcohol use behavior of a typical student to be higher than their own self-reported behavior, are consistent (Page et al, 2008) with findings of studies among University students in North-America (Borsari & Carey, 2003;Kypri & Langley, 2003) and Western Europe (Franca et al, 2010;McAlaney & McMahon, 2007). Our findings are also consistent with findings in a study conducted among adolescents in Hungary, Slovak Republic, Czech Republic and Romania (Page et al, 2008) which supports the notion that this is a general pattern.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings, that a high proportion of students estimated the alcohol use behavior of a typical student to be higher than their own self-reported behavior, are consistent (Page et al, 2008) with findings of studies among University students in North-America (Borsari & Carey, 2003;Kypri & Langley, 2003) and Western Europe (Franca et al, 2010;McAlaney & McMahon, 2007). Our findings are also consistent with findings in a study conducted among adolescents in Hungary, Slovak Republic, Czech Republic and Romania (Page et al, 2008) which supports the notion that this is a general pattern.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, some European studies have examined misperceptions of alcohol use among University students in the UK (McAlaney & McMahon, 2007) and France (Franca, Dautzenberg, & Reynaud, 2010) and have reported findings comparable to those of NorthAmerican studies.…”
Section: Introductionmentioning
confidence: 74%
“…Since then, a large number of studies have shown that these so-called normative misperceptions about substance misuse behaviours occur in a variety of countries and settings (Wolfson, 2000;Haines et al, 2003;Kypri & Langley, 2003;Lintonen & Konu, 2004;McAlaney & McMahon, 2007;Bewick et al, 2008;Hughes et al, 2008;Page et al, 2008;Franca et al, 2010). These misperceptions cause worry since people are strongly influenced by what they perceive to be the norms of their peer group; a phenomenon that has been studied extensively in psychology following the work of Asch (1951).…”
Section: Introductionmentioning
confidence: 99%
“…It originates from a study in the American college system, in which it was noted that students tended to overestimate how heavily and frequently their peers drank alcohol (2) . Similar misperceptions have now been documented at numerous college sites in the USA (3,4) and also in student and adolescent populations in Scotland (5) , England (6) , Australia (7) , New Zealand (8) , Finland (9) Hungary, Slovakia, Romania, the Czech Republic (10) , and France (11) . The social norms approach aims to change behaviour by correcting these misperceptions through the use of a variety of mass media campaigns and personal feedback.…”
Section: Introductionmentioning
confidence: 98%